The Role of Organizational Communication in Improving Work Effectiveness at the Mangliawan Village Office, Malang Regency - Ferry Indra Sukma; Siswandoyo, Eko Budi; Soeryono Putri, Meynandha Salshabhilla (oneamd.com, 2024)
This study aims to analyze the role and influence of organizational communication on improving work effectiveness with a case study at the Mangliawan Village Office, Pakis District, Malang Regency. The research focus includes the implementation of vertical (superior-subordinate) and horizontal (inter-staff) communication, its relation to fulfilling employee needs based on Maslow's theory, as well as the identification of obstacles and improvement strategies. This study uses a qualitative approach with a descriptive case study method. The research results show that organizational communication at the Mangliawan Village Office has been running well and contributes significantly to work effectiveness. Open vertical communication has been created where superiors' instructions are easily understood and feedback from subordinates is accepted. Horizontal communication is characterized by a strong sense of family, empathy, and mutual cooperation. The fulfillment of employees' physiological, safety, social, esteem, and self-actualization needs also encourages work motivation. However, obstacles were found such as potential task duplication (job overlap) in certain situations and a reward system that is still informal. Effective organizational communication, built on message clarity, harmonious relationships, and fulfillment of employee needs, has proven to be a key factor in improving work effectiveness at the Mangliawan Village Office.